Antioxidant and antimicrobial activities of shorea kunstleri - Daud, Siti Suria; Bakhtiar, M. Taher; Darnis, Deny Susanti; Mohamed Zaffar Ali, Mohamed Amiroudine; Tengku Zakaria, Tengku Muhamad Faris Syafiq (Coastal Life Medicine Media co., Limited, 2014)
Objective: To evaluate antioxidant and antimicrobial activities of stembark of Shorea kunstleri together with analysis of phytochemical and total phenolic contents.